PENINGKATAN PROSES DAN HASIL PEMBELAJARAN IPA MENGGUNAKAN PENDEKATAN KONTEKSTUAL DI SEKOLAH DASAR - Rita Zunarti; Subhanadri Subhanadri (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
This study began with the low learning outcomes of science students in grade V SDN 223 /II Rantau Embacang. This study aims to improve the science learning outcomes by using a contextual approach. This type of research is classroom action research. This research was conducted in two cycles. Every cycle there are activities of planning, implementation, observation and reflection. The results of this study indicate that the use of contextual approaches can improve the learning outcomes of science students in grade V SDN 223 / II Simp. Rantau Embacang. The results showed that the Natural Science Learning using the contestant approach class V SDN 223 /II Simp. Rantau Embacan at the implementation stage of the action on the teacher aspect in accordance with observers' observations achieved good success and aspects of students achieving good success. The average value of student learning outcomes at meeting 1 is 79, 48 and meeting II is 80.63. Student learning outcomes in the second cycle reached an average value of 80%. Based on that, this study ended in cycle II.